Physiological profile of elite Greek gymnasts - Dallas, G.; Zacharogiannis, E.; Paradisis, G. (Journal of Physical Education and Sport, 2013)
The purpose of this study was to investigate physiological characteristics of female and male Greek international artistic gymnasts during pre-competition season. Nine female (mean ± sd: age 16.89 ± 3.62 years, height 150.17 ± 7.06 cm, body mass 46.07 ± 9.26 kg) and eleven male (mean ± sd: age 17.73 ± 1.55 years, height 161.18 ± 6.96 cm, body mass 58.09 ± 8.21 kg) international level artistic gymnasts recruited to participate in this study. They were evaluated for upper limps maximal muscular power, explosive strength of lower limp (vertical jump), maximal power of knee extensors and flexors, flexibility of hamstring and lower back, maximal oxygen consumption (VO2max), running speed at VO2max (vVO2max), running speed at ventilatory threshold (VT), HRmax, maximal blood lactate concentration, maximal alactic leg power (Wingate test) and maximal leg frequency. Females mean %body fat was significantly greater compared with the males (p<0.01). Flexibility and VO2max was not different between females and males gymnasts (p>0.05). On the contrary there was significant difference for female and male gymnasts on mean maximal blood lactate concentration, anaerobic alactic maximal leg power, maximal leg frequency, maximal explosive leg power (vertical jump), knee extensors and flexors power, shoulders flexors and arm extensors (bench press) maximal power, arm pulls, vVO2max, VT, and HRmax (p<0.05). The findings of the present study suggest that the physiological characteristics of international level gymnasts may play an important role during training. This provides coaches with valuable information on fitness parameters and helps to design individual training programs and evaluate responsiveness to training stimulus with the aim to maximize training adaptations and event specific performance.